Cocaine Directly Inhibits α6-Containing Nicotinic Acetylcholine Receptors in Human SH-EP1 Cells and Mouse VTA DA Neurons - Chen, Dejie; Gao, Fenfei; Ma, Xiaokuang; Eaton, Jason Brek; Huang, Yuanbing; Gao, Ming; Chang, Yongchang; Ma, Zegang; Der-Ghazarian, Taleen; Neisewander, Janet; Whiteaker, Paul; Wu, Jie; et al. (Frontiers in Pharmacology, 2019)
Alpha6-containing nicotinic acetylcholine receptors are primarily found in neurons of the midbrain dopaminergic (DA) system, suggesting these receptors are potentially involved in drug reward and dependence. Here, we report a novel effect that cocaine directly inhibits α6N/α3Cβ2β3-nAChR (α6*-nAChRs) function. Human α6*-nAChRs were heterologously expressed within cells of the SH-EP1 cell line for functional characterization. Mechanically dissociated dopaminergic (DA) neurons from mouse ventral tegmental area (VTA) were used as a model of presynaptic α6*-nAChR activation since this method preserves terminal boutons. Patch-clamp recordings in whole-cell configuration were used to measure α6*-nAChR function as well as evaluate the effects of cocaine. In SH-EP1 cells containing heterologously expressed human α6*-nAChRs, cocaine inhibits nicotine-induced inward currents in a concentration-dependent manner with an IC50 value of 30 µM. Interestingly, in the presence of 30 µM cocaine, the maximal current response of the nicotine concentration-response curve is reduced without changing nicotine’s EC50 value, suggesting a non-competitive mechanism. Furthermore, analysis of whole-cell current kinetics demonstrated that cocaine slows nAChR channel activation but accelerates whole-cell current decay time. Our findings demonstrate that cocaine-induced inhibition occurs solely with bath application, but not during intracellular administration, and this inhibition is not use-dependent. Additionally, in Xenopus oocytes, cocaine inhibits both α6N/α3Cβ2β3-nAChRs and α6M211L/α3ICβ2β3-nCAhRs similarly, suggesting that cocaine may not act on the α3 trans-membrane domain of chimeric α6N/α3Cβ2β3-nAChR. In mechanically isolated VTA DA neurons, cocaine abolishes α6*-nAChR-mediated enhancement of sIPSCs. Collectively, these studies provide the first evidence that cocaine directly inhibits the function of both heterologously and naturally expressed α6*-nAChRs. These findings suggest that α6*-nAChRs may provide a novel pharmacological target mediating the effects of cocaine, and may underlie a novel mechanism of cocaine reward and dependence.